Integration of Digital Preaching in the Formation of Generation Z Spirituality in the Digital Era - Ainun Lutfiya; Nasrulloh Nasrulloh (Penerbit Hellow Pustaka, 2026)
This study aims to analyze how Generation Z accesses, interprets, and shapes religious spirituality through interactions with digital da'wah and to identify the mechanisms for integrating Quranic and Hadith values ​​within this process. This study uses a qualitative approach through in-depth interviews with Gen Z participants and literature analysis to explore content consumption patterns, the tabayyun process, internalization of values, and self-control practices. The results indicate that exposure to digital da'wah does not automatically produce religiosity, but requires source selection, verification of truth, inner reflection, and the application of values ​​such as adab (ethics), honesty, and tazkiyat al-nafs (observance of the self). This study formulates an integrative model for the formation of Gen Z's digital spirituality, consisting of the stages of da'wah exposure, content selection, tabayyun (observance of meaning), internalization of meaning, and implementation of digital ethics. These findings provide theoretical contributions to the study of digital media-based Islamic spirituality and practical support for educators and da'wah stakeholders in developing credible, reflective, and contextual da'wah strategies for the younger generation.